Influencia de la edad de vacunación con la vacuna B. abortus S19 en la respuesta serológica inducida en terneras - Meglia, G. (2011)
Brucellosis is an infectious disease that affects bovine, among other species, producing loses through infertility. The objective of the present work was to assess the effect of vaccination against brucellosis over the humoral immune response in two groups of different age beef calves, as well as to determine the degree of relationship between 2 mercapto-ethanol and fl uorescence polarization assay diagnosis in BPA positive animals. On average, group 1 was vaccinated at 3,5 and group 2 at 7,5 months of age. The animals were bled monthly, and the IgM and/or IgG, and IgG were assessed through Wright and 2-ME, respectively. The serum concentrations of immunoglobulin were significantly higher in the group 2 in relation to group 1. In animals BPA (+), FPA showed significantly lower positive values in relation to 2-ME. Moreover, the group of animals vaccinated at younger age showed positive serum FPA results for a period longer than 90 days in relation to the adult vaccinated ones, exhibiting an unexpected behavior.